A therapist’s perspective of a financial planning course: Implications for financial therapy education and trainings - Megan Ann McCoy; Jerry Gale; Megan Ford; Ronald G McCoy II (Journal of Financial Therapy, 2013)
This paper presents the autoethnography of a doctoral Marriage and Family Therapy (MFT) student studying finances in a graduate course. A dataset in the form of field notes was created through recording observations and reflective journaling during the 15 week financial planning course. This data set included observations and insights on various skills and knowledge that would be helpful for conducting financial therapy, the professional and personal growth of a therapist integrating finances into her clinical work, and evaluations regarding how financial courses can be beneficial for therapists and planners who are interested in the interaction between relational and financial issues. Based on the first author’s experiences, reflections and conversations with the second author, four themes were developed. The themes were: (a) Seeing the Unnoticed: Challenging Implicit Assumptions, (b) Critically Examining My Own Money Scripts, (c) What can Therapists Learn From the Financial Discipline, and (d) What Financial Planners can Learn from the Clinical Disciplines. Implications for the burgeoning field of financial therapy are discussed, with special attention given to cross-discipline education and training.
Keywords: Financial therapy; financial planning; financial counseling; marriage and family therapy